The Effect of Liquidity and Leverage on Profitability (Case Study on PT Industri Jamu and Farmasi Sido Muncul, Tbk) - Saprudin Saprudin; Samuel Soaloon Sitompul; Rina Dameria Napitupulu; Revan Andhitiyara (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The Effect of Liquidity and Leverage on Profitability aims to test the effect of whether Liquidity and Leverage affect Profitability in sidomuncul herbal and pharmaceutical industry companies listed on the Indonesia Stock Exchange (IDX).The method used in this study is a multiple regression method to determine the influence of variables related to the study.The results of the study revealed a simultaneous F test, namely the calculated value F = 5.350. The value of 5,350>3.47, thus Ho is rejected and H3 is accepted, means that there is an influence between Liquidity (X1) and Leverage (X2) simultaneously on the Profitability (Y) of companies listed on the Indonesia Stock Exchange in 2016-2021.Based on this, it is recommended that further research use other methods in classifying, using different measurements such as variable size using the stock market value log size, profitability using operating ratio, return to equity, return on investment, so that the sample to be used becomes wider so that subsequent researchers can describe the actual situation as a whole.